Efecto de dos fitohormonas auxínicas (Ácido indolacético y ácido indolbutírico) para la propagación asexual de chamburo (Vasconcellea pubescens) a través de estacas - Navarrete Rendón, Carlita Lisbeth (2025)
Chamburo (Vasconcellea pubescens) is a crop of great economic and cultural importance. This research was established to evaluate the effect of two auxin phytohormones AIA and AIB, for asexual propagation through cuttings in chamburo. The objectives were: i) Evaluate the most effective growth phytohormone for the propagation of chamburo. ii) Establish the phytohormone dose that stimulates greater root development in the asexual propagation of chamburo for transplantation. iii) Determine the most efficient treatment for the propagation of chamburo. The treatments studied were the combination between FA (Phytohormones), and FB (Dose of concentrations). For this study, a completely randomized design (DCA) in a 2x4 factorial arrangement with three replications plus 1 absolute control was used. The type of analysis that was performed was analysis of variance, Tukey's test at 5% using the statistical software Infostat. In addition, a correlation analysis and simple linear regression were performed. The agronomic variables evaluated were: days to sprouting (DB), number of shoots per cutting (NBE), shoot length (LB), number of leaves per cutting (NHE), cutting diameter (DE), cutting length (LE), number of roots (NR), root length (LR) and survival percentage (PS). The statistical results showed that the best treatment was (Indoleacetic Acid + 6 mg / l) promoted a highly favorable physiological response in the propagation of chamburo cuttings, stimulating essential processes such as cell division, and tissue elongation. This combination optimized the emission of shoots, leaf formation and expansion, root development, resulting in more vigorous, balanced and uniform growth. The synergistic action between the growth regulator and adequate concentration favored greater efficiency in the absorption of nutrients and water, strengthening the structure of the seedlings and improving their establishment capacity.